Experimental T-2 toxicosis in sheep. - Friend, S C (1983)
Lambs received T-2 toxin at a rate of 0.6 or 0.3 mg/kg body weight per day in a protein reduced diet for 21 days to study the immunological and pathological effects of T-2 toxin in sheep. Blood was collected before T-2 treatment and on days 7, 14 and 21 of the trial for hematological and biochemical examination and for the separation of peripheral blood lymphocytes for the mitogen assay. Myeloid:erythroid ratios were determined from sternal bone marrow samples taken a day before T-2 treatment began, on day 12 and at death (day 22). Lambs treated with 0.6 mg/kg body weight of T-2 toxin daily were leukopenic on day 7 and lymphopenic on days 7 and 14. Also, on day 7, the mitogenic responses of these lambs to the B-cell mitogen, lipopolysaccharide, were significantly depressed and prothrombin times were prolonged. At necropsy, lymphoid atrophy of mesenteric lymph nodes and spleens was most marked in lambs treated with 0.6 mg/kg body weight of T-2 toxin per day. To the authors' knowledge, this is the first report of leukopenia, lymphopenia and lymphoid depletion in ruminants fed T-2 toxin.